The Nexus between Leadership and Implementation of Education Infrastructure Development Policy Goals in Tanzania: Reflections from Kinondoni Municipal Council - Mdanya, Theresia; Malipula, Mrisho, Dr (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2023)
This study assessed the association between leadership attributes and qualities in the implementation of education infrastructure development policy goals in Tanzania using Kinondoni Municipal Council as a case. A concurrent mixed-method triangulation of qualitative and quantitative data was employed to explore the nexus between leadership attributes and qualities in implementing education infrastructure development policy goals in Tanzania. The data used in this study was garnered from face-to-face interviews with 92 respondents recruited from a population of 288 Kinondoni Municipal Council workers and a review of documentary sources relevant to the study. The application of primary data from interviews and desk reviews allowed triangulation of the findings garnered from the two data sources, which usefully enriched and enhanced the validity and reliability of the findings. Quantitative data were analyzed using IBM statistics software to determine frequencies and run association tests, while qualitative data were analyzed thematically and discussed descriptively. The study found that collaborative leadership, public policy advocacy, coordination, effective dialogue with the community, and leaders’ commitment to being leadership attributes are significantly positively associated with implementing education infrastructure development policy goals in Kinondoni Municipal Council. Furthermore, Interpersonal communication, integrity, accountability, empathy, and vision significantly influence the implementation of education infrastructure development policy goals in the Kinondoni Municipal Council. In this regard, efforts should be put in place to improve the qualities and attributes among leaders to maximize the implementation of education infrastructure development policy goals.